Marker-assisted introgression of fecundity mutation into Barbarine sheep breed under low input production system - Bedhiaf-Romdhani, S.; Baazaoui, Imen; Arari, Emna; Lahmar, Mustapha; Letaief, Neyrouz; Hemdene, Mounir; Rekik, Mourad; Haile, Aynalem (Springer, 2023)
Fecundity gene introgression has become an economical method to improve sheep prolificacy in developing countries. The FecXBar and FecGH mutations are variants of the BMP15 and GDF9 sheep genes, respectively, identified in Tunisian Barbarine sheep prolific line “W-INRAT,” created through a prolificacy-based selection program. The first mutation caused increased prolificacy in heterozygous state and sterility in homozygous ewes. The aim of this work was to increase the number of effective carriers by the introgression of fecundity mutation into non-carrier conventional flocks based on a marker-assisted breeding program. The genotyping was carried out to follow up on the segregation of prolificacy mutation. The conventional ewes, raised in state farms of Tunisia and inseminated by “W-INRAT” rams, yielded 100% carriers females at heterozygous state. These females were selected to be inseminated with conventional rams and produced carriers’ lambs with 66.7% males and 33.3% females. The prolific males will be kept in breeding centers to disseminate the fecundity mutation in commercial flocks. This approach facilitates the dissemination of fecundity genes and contributes to livelihood improvement in communities raising Barbarine sheep.